Peran Strategis Kepala Sekolah dalam Peningkatan Kinerja Guru di SMP YPPK Bonaventura Sentani, Provinsi Papua - Andinus Yanengga; Barton Wenda; Marthinus Kayame (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This research aims to investigate the strategies implemented by the school principal in improving teacher performance, while also identifying the supporting and inhibiting factors and assessing the impacts of these strategies. The study adopts a qualitative case study approach, involving seven participants comprising the principal, teachers, school committee representatives, and a school supervisor. Data were collected using detailed interviews, on-site observations, and examination of relevant documents. The analysis process involved condensing the data, organizing it systematically, and then forming conclusions based on the findings. To maintain the credibility and reliability of the findings, several validation procedures were applied, including extended engagement in the field, careful and continuous observation, triangulation of data sources, peer discussions, and in-depth case analysis. The results reveal that teachers demonstrate a strong sense of responsibility in carrying out their duties, while discipline is maintained through the consistent implementation of rules and corrective measures. The principal applies a fair and needs-based approach in managing teachers, which contributes to a high level of job satisfaction. Work management is organized systematically through clear task allocation and proportional workload distribution. Furthermore, incentives are provided in accordance with assigned responsibilities, and the principal actively acknowledges teachers’ achievements. These practices collectively foster increased motivation and contribute to improved overall performance within the school.